2003
DOI: 10.1016/s0921-5093(02)00169-7
|View full text |Cite
|
Sign up to set email alerts
|

Short crack initiation and growth at 600°C in notched specimens of Inconel718

Abstract: The natural initiation and growth of short cracks in Inconel ® 718 U-notch specimens has been studied at 600 o C in air. U notches were introduced through broaching, and hardness traces and optical microscopy on cross sections through the U notch broaching showed that the broaching process had introduced a deformed, work hardened layer. Fatigue tests were conducted under load control using a 1-1-1-1 trapezoidal waveform, on specimens with as-broached and polished U-notches. Multi-site crack initiation occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 33 publications
9
78
0
Order By: Relevance
“…Previous work by the authors on Batch A specimens [25] demonstrated that primary carbides at or close to the surface of IN718 oxidised at elevated temperatures, and there was a substantial volume expansion associated with oxidation. This was observed in unstressed specimens and U-notch fatigue specimens exposed at 550 o C and 600 o C in air.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous work by the authors on Batch A specimens [25] demonstrated that primary carbides at or close to the surface of IN718 oxidised at elevated temperatures, and there was a substantial volume expansion associated with oxidation. This was observed in unstressed specimens and U-notch fatigue specimens exposed at 550 o C and 600 o C in air.…”
Section: Discussionmentioning
confidence: 95%
“…Volume expansion of oxidising primary carbides was identified as a mechanism of environmentally assisted crack propagation in notch-rupture tests on IN718 [21] . The role of oxidised primary carbides in fatigue crack initiation has also been studied [22,23,24,25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the oxidation behavior at intermediate temperature of IN718 alloy was controlled by the oxidation of NbC carbide and the formation of Cr 2 O 3 and Fe 2 O 3. [7,8] The Cr 2 O 3 would preferentially form at grain boundaries, which inhibits the progression of oxygen along grain boundaries. However, the Cr contents were not high enough to form continuous protective oxide layer at the initial oxidation stage, therefore other elements can be oxidized within the grain.…”
Section: Hot Corrosionmentioning
confidence: 99%
“…[1,3,[8][9][10]). The effect of grain size reduction ,assumed to be beneficial on fatigue lives, was more particularly studied for conventional and DA 718 alloys (see e.g.…”
Section: Fatigue Crack Initiation Sitesmentioning
confidence: 99%